PENTINGNYA ILMU GIZI DAN POLA HIDUP SEHAT DENGAN MENGONSUMSI SAYUR DAN BUAH SETIAP HARI DI MTS ALKHAIRAT MOUTONG DESA MOUTONG TENGAH KEC.MOUTONG KAB. PARIGI MOUTONG PROVINSI SULAWESI TENGAH - Nurmiya Harmain; Deby Sinta Darise (LPPM Universitas Bina Mandiri Gorontalo, 2024)
There are still many people in Moutong Tengah Village who do not fully understand the importance of nutrition and a healthy lifestyle by consuming vegetables and fruit every day, so this research aims to make the community aware by providing knowledge of the importance of nutrition and a healthy lifestyle by consuming vegetables and fruit every day. The method used in socialization and educational activities was lectures and discussions on the theme which was held on July 27 2023 with 30 eighth grade students participating. The results of the implementation of socialization activities that have been carried out show that there are significant mindsets and attitudes from the community and students at MTs Alkhairat Moutong: 1) the importance of nutrition; 2) healthy lifestyle; 3) consume vegetables and fruit every day in the community, especially at MTs Alkhairat Moutong. For this reason, this socialization activity can produce a healthy young generation for the future of the nation, especially students at MTs Alkhairat Moutong, Middle Moutong Village, Parigi Moutong Regency, from the importance of nutrition and a healthy lifestyle by consuming vegetables and fruit every day.